Concomitant differentiation of a population of mouse embryonic stem cells into neuron‐like cells and schwann cell–like cells in a slow‐flow microfluidic device. Issue 1 (17th November 2016) - Ramamurthy, Poornapriya; White, Joshua B.; Yull Park, Joong; Hume, Richard I.; Ebisu, Fumi; Mendez, Flor; Takayama, Shuichi; Barald, Kate F.
Abstract : Background : To send meaningful information to the brain, an inner ear cochlear implant (CI) must become closely coupled to as large and healthy a population of remaining spiral ganglion neurons (SGN) as possible. Inner ear gangliogenesis depends on macrophage migration inhibitory factor (MIF), a directionally attractant neurotrophic cytokine made by both Schwann and supporting cells (Bank et al., 2012). MIF‐induced mouse embryonic stem cell (mESC)‐derived "neurons" could potentially substitute for lost or damaged SGN. mESC‐derived "Schwann cells" produce MIF, as do all Schwann cells (Huang et al., 2002a a; Roth et al., 2007; Roth et al., 2008) and could attract SGN to a "cell‐coated" implant.Results : Neuron‐ and Schwann cell–like cells were produced from a common population of mESCs in an ultra‐slow‐flow microfluidic device. As the populations interacted, "neurons" grew over the "Schwann cell" lawn, and early events in myelination were documented. Blocking MIF on the Schwann cell side greatly reduced directional neurite outgrowth. MIF‐expressing "Schwann cells" were used to coat a CI: Mouse SGN and MIF‐induced "neurons" grew directionally to the CI and to a wild‐type but not MIF‐knockout organ of Corti explant.Conclusions : Two novel stem cell–based approaches for treating the problem of sensorineural hearing loss are described. Developmental Dynamics 246:7–27, 2017 . © 2016 Wiley Periodicals, Inc. Key findings: We have used a simple "ultra‐slow‐flow" microfluidic device to differentiate a single population of mouse embryonic stem cells (mESCs) into neuron‐like cells and Schwann cell–like cells, using one of three different neuron‐inducing agents and Neuregulin, a Schwann cell–inducing agent. The agents used to induce the neuronal phenotype were nerve growth factor (NGF), ciliary neurotrophic factor (CNTF), or macrophage migration inhibitory factor (MIF), the neurotrophic cytokine that is critical for inner ear development in vertebrates. Use of different agents resulted in differences in neuronal properties and influenced the observed early steps in myelination. We tested the influence of MIF on directional neurite outgrowth from neuron‐like cells to the Schwann cell–like cells by inhibiting MIF biochemically or by blocking its effects with a function‐blocking monoclonal antibody. Statistically significant reductions in directed neurite outgrowth were observed under all conditions, but especially if MIF was used as the neural‐inducing agent. We then "coated" cochlear implants with alginate hydrogel layers containing the MIF‐producing Schwann cell–like cells. Primary mouse statoacoustic ganglion neurons, spiral ganglion neurons (SGN), and MIF‐induced neuron‐like cells exhibited directed outgrowth in vitro to two types of cochlear implants: implants meant for human implantation and implants used in animal (e.g., gerbil) studies. No directed outgrowth from any of the "neuronal" subtypes was seen toward a "bare" or hydrogel‐coated cochlear implant or implants coated with undifferentiated embryonic stem cells. Macrophage migration inhibitory factor (MIF)‐induced neuron‐like‐cells exhibited directed neurite outgrowth to a wild type mouse Organ of Corti explant in culture but not towards a MIF‐knock out organ of Corti explant.